Prediction of residual stresses in ball burnishing TI6AL4V thin sheets - Livatyali, Haydar; Has, Ergul; Turkoz, Mevlut (SPRINGER LONDON LTD, 2020)
The static-implicit finite element method was used to simulate the low plasticity ball burnishing process using two-dimensional (2-D) and three-dimensional (3-D) models. The simulations were performed using an elastic-rigid strain hardening plastic flow model. The residual stress distribution along the surface layer of the Ti6Al4V thin sheet is predicted, and the results are compared with limited experimental data from the industry. The simulated residual stresses matched with the measured ones in terms of trends; however, some deviations were observed for the peak and boundary values. The 2-D model is practical to construct, and the simulations are fast; however, it does not provide the planar stress distribution. The 3-D model is more realistic, yet still very sensitive to boundary conditions as well as friction. More realistic results are possible with large models where the effects of boundary conditions get weaker.
Keywords: Low plasticity ball burnishing (LPB); Finite element method; Residual stress; PARAMETERS; ROUGHNESS; ALLOY; Automation & Control Systems; Engineering